Drying Shrinkage Properties and Crack Development of Mortar Containing Sandy Clay - Koh, Hwei Shan; Koh, Heng Boon (Recent Trends in Civil Engineering and Built Environment, 2022)
The global demand for mortar has prompted the worldwide utilization of fine aggregates. Environmental issues have arisen as a result of the depletion of fine aggregates. In this study sandy clay is used to replace natural fine aggregate to prepare the mortar. The experimental works were focused on the drying shrinkage properties and crack development of mortar with varying proportions of sandy clay. Five types of mortar with 0%, 25%, 50%, 75% and 100% of sandy clay were prepared. A total of 10 prism specimens with the dimensions of 75mm x 75mm x 300mm length subjected to air curing under ambient temperature were prepared to determine the drying shrinkage properties. While, another 10 panel specimens of 300mm x 300mm x 15mm thick were used to study the crack development. 5 panels were kept indoor (cured) and another 5 panels were exposed to the sun and rain (uncured). Both of the drying shrinkage and crack development tests were carried out for 60 days. From the experimental results, mortar containing 75% and 100% sandy clay achieved much higher drying shrinkage. Meanwhile, panels (75% and 100%) under uncured conditions were shown significant crack development. The optimum percentage of sandy clay used in mortar is 25% with acceptable drying shrinkage properties without significant crack for both cured and uncured conditions.